Severity of Occlusal Disharmonies in Down Syndrome - Danielle Bauer; Carla A. Evans; Ellen A. BeGole; Larry Salzmann (Hindawi Limited, 2012)
Objective. To quantify the severity of malocclusion and dental esthetic problems in untreated Down syndrome (DS) and untreated non-Down syndrome children age 8-14 years old using the PAR and ICON Indices. Materials and Methods. This retrospective study evaluated pretreatment study models, intraoral photographs, and panoramic radiographs of 30 Down syndrome and two groups of 30 non-Down syndrome patients (private practice and university clinic) age 8-14 years. The models were scored via PAR and ICON Indices, and descriptive characteristics such as Angle classification, missing or impacted teeth, crossbites, open bites, and other dental anomalies were recorded. Results. The DS group had significantly greater PAR and ICON scores, as well as 10 times more missing teeth than the non-DS group. The DS group possessed predominantly Class III malocclusions, with the presence of both anterior and posterior crossbites in a majority of the patients. The non-DS group had mostly Class I or II malocclusion with markedly fewer missing teeth and crossbites. The DS group also had more severe malocclusions based upon occlusal traits such as open bite and type of malocclusion. Conclusion. The DS group had very severe malocclusions, while the control group from the university clinic had more severe malocclusions than a control group from a private practice.